Triggers of Exacerbation in Chronic Urticaria and Recurrent Angioedema—Prevalence and Relevance (2021)
Patients with urticaria and angioedema often have triggers that cause an outbreak or a swelling episode or worsen their chronic condition. Exploring these factors with each patient may result in better understanding and control of their disease. Patients should be advised to avoid known triggers, if feasible, or prepare to prevent or control an exacerbation with appropriate pretreatment if avoidance is not possible. In this review, we describe and discuss a variety of factors for which there is evidence that they cause or exacerbate chronic spontaneous urticaria and angioedema. These potentially exacerbating factors include drugs, food additives, and naturally occurring pseudoallergens, mental stress, and trauma.